Ingane Yamalungelo (Book collections on Project MUSE., 2019)
IsiZulu drama book titled 'Ingane Yamalungelo' translated as 'Child of Rights' is a drama book written for reading. It can be changed to be played in real places. This drama talks about the new theme for children using their rights the way that is unacceptable. The main character of the drama is Zethu, she uses her rights with an unacceptable way where she shows disrespect to her parents. This drama has a conflict between Zethu and her parents where they do not see things on the same way. Reader, read it for yourself and you will find it if the main character is able to free herself from the problems she put herself in because of not using her rights correct. In this drama the writers encourage the children to exercise their rights correct and respect their parents because if they do not, they may find themselves facing big problems with their life.